Snail shell as an efficient mineral feedstuff for layer hens: Effects and optimum rate - HOUNDONOUGBO, M. FRÉDÉRIC; CHRYSOSTOME, CHRISTOPHE ACHILLE A. MAHUSSI; ODOULAMI, ROMARIC C; CODJIA, JEAN TIMOTHE CLAUDE (My University, 2012)
An experiment was carried to determine the optimal rate of snail shell in diet of layer hens and its effects on productivity and quality of eggs. A total of 90 ISA Brown laying hens having 60 weeks-old and 87.0 ± 5.5 % as average laying rate were divided into 5 dietary treatments. In diets, the oyster shell was substituted by snail shell at 0% (SS0), 25% (SS0), 50% (SS50), 75% (SS75) and 100% (SS100). Completely Randomized Design was used. Hens were housed in Californian cages and each diet was delivered to nine cages (replications) of two hens each. The results demonstrated that the laying rate improved significantly in dietary treatments SS25 and SS50 (P < 0.05), whereas, eggs weight and eggshell thickness were significantly higher in control group SS0. The daily feed intake was significantly lower in SS100 and the feed conversion ratio was significantly improved in SS25 and SS50 treatments. The Haugh units and albumen height of eggs were similar between diets. The feed costs were significantly lower in SS25 (27.6 FCFA/egg) and SS50 (27.4 FCFA/egg) than in SS0 (29.9 FCFA/egg), SS75 (29.6 FCFA/egg) and SS100 (28.16 FCFA/egg). It can be concluded that up to 50% of oyster shell can be efficiently substituted by snail shell in diet of laying hens.
Keywords: Benin; calcium; diet; egg; poultry